Effects of copper sulfate and zinc oxide on weanling pig growth and plasma mineral levels - Shelton, N.W.; Tokach, Michael D.; DeRouchey, Joel M.; Hill, G.M.; Amachawadi, R.G.; Nagaraja, Tiruvoor G.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 216 weanling pigs (PIC TR4 × 1050, initially 13.6 lb and 21 d of age) were used in a 42-d growth trial to compare the effects of supplemental zinc and copper and changing mineral regimens on growth performance and plasma mineral levels. The 6 dietary treatments included a 2 × 2 factorial arrangement with main effects of added copper from copper sulfate (0 or 125 ppm) and added zinc from zinc oxide (0 or 3,000 ppm from d 0 to 14 and 0 or 2,000 ppm from d 14 to 42). For the final 2 treatments, either zinc oxide alone or the combinations of zinc and copper were fed from d 0 to 14, with copper sulfate fed from d 14 to 42. There were 6 pens per treatment with 6 pigs per pen. All diets were supplemented with an additional 165 ppm zinc and 16.5 ppm copper from the trace mineral premix. Plasma was collected from 2 pigs per pen on d 14 and 42. From d 0 to 14, ADG, ADFI, and F/G were improved (P < 0.04) with the addition of dietary zinc. Copper supplementation also tended to increase (P < 0.07) ADFI from d 0 to 14. From d 14 to 42, added copper increased (P < 0.003) ADG and ADFI. Over the entire trial, continuous supplemental zinc increased (P < 0.03) ADG and tended to increase (P < 0.09) ADFI. Dietary copper also increased (P < 0.004) ADG and ADFI when fed from d 0 to 42. The most advantageous values for ADG and ADFI were seen in the treatment containing high levels of zinc from d 0 to 14 and high copper levels from d 14 to 42. The addition of either zinc or copper increased (P < 0.02) feed cost per pound of gain. However, income over feed cost was improved (P < 0.006) with the addition of copper, with the greatest value obtained when high zinc was fed from d 0 to 14 and high copper was fed from d 14 to 42. Plasma zinc levels were increased (P < 0.001) with zinc supplementation on d 14. These results indicate the optimal mineral regimen was supplementing zinc oxide from d 0 to 14 and copper sulfate from d 14 to 42.
Keywords: Copper; Growth promotion; Zinc; Swine